Influence of filler-binders on ibuprofen iablets with direct compression method - Hadisoewignyo, Lannie; Teny, Gracesya Florensya; Handayani, Elok Tri; Yunita, Beby (Indonesian Journal of Pharmacy, 2011)
Ibuprofen  is  a  active  ingredient  that  have  low  melting  point,  but  it  has poor  flowability,  and  poor  compactibility,  this  causes  ibuprofen  tablets  are  not suitable  to  be  made  by   direct  compression  method.   The  use  of  appropiate filler-binders  can  improved  the  flow  properties  and  compactibility  powder  that can be made  by  direct compression. Filler binders  commonly use  are  Avicel PH 102, Emcompress, SDl, and Starch 1500. Formula tablet ibruprofen using Avicel PH 102 as filler-binder will produce tablet with good hardness, low friability, fast disintegrating,  and  high  dissolution.  This  is  because  the  hydrophilic  properties and plastic deformation which is owned by Avicel PH 102.Key words:Ibuprofen, Avicel PH 102, direct compression